2018
DOI: 10.1128/mspheredirect.00545-17
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Reconstitution Does Not Cause Bone Loss in Germ-Free Mice

Abstract: The microbiota has been shown to be an important regulator of health and development. With regard to its effect on bone health, a previous study has suggested that gut microbes negatively impact bone density. However, we show here that this is not generalizable to all microbial communities and mouse strain backgrounds. Our results demonstrate that colonization of mice, both outbred and inbred strains, did not have a major impact on bone health. The identification of microbial communities that do not negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 47 publications
1
47
2
Order By: Relevance
“…Our studies show that the microbiota depletion seen at the 2‐week time point of antibiotic treatment did not affect bone density measures. Our results are similar to some germ‐free mouse studies . Studies in germ‐free mice, however, are inconsistent in terms of bone growth and density (increase, decrease, no change) .…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Our studies show that the microbiota depletion seen at the 2‐week time point of antibiotic treatment did not affect bone density measures. Our results are similar to some germ‐free mouse studies . Studies in germ‐free mice, however, are inconsistent in terms of bone growth and density (increase, decrease, no change) .…”
Section: Discussionsupporting
confidence: 85%
“…Antibiotics save countless lives and can prevent the spread of pathogenic bacteria; however, a significant side‐effect of antibiotics is that they also deplete the commensal microbiota . Increasing numbers of studies demonstrate a role for the intestinal bacteria, as well as its composition in the regulation bone health . In the present study, we found that repopulation of the microbiota following acute antibiotic treatment results in dysbiosis, increases intestinal permeability, and has a detrimental effect on trabecular bone health.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations